Conflict Management Practices of Customs Broker Practitioner: A Comparative Approach - Doyo, Joan R.; Dante, Jr, Julian M.; Gutierrez, Ernell Bautista; De Vera, Rommel C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Conflict is inevitable in all organizations as well as in all professions and with proper management its negative effect can always be mitigated. This research utilized a descriptive-comparative approach and determined the extent of conflict management practices in customs brokerage from one hundred eighty professional brokers. Results revealed that customs brokers highly practiced the following conflict management: Competing, Collaborating, Compromising, Avoiding, and Accommodating. Likewise, results further revealed that there is no difference in the extent of practices of conflict management by customs brokers when industry, years in practice, and age are considered.